Specialized etherboot architecture for LTSP (SEAL) - Diaz, Karl Oliver D. (2006)
The computers of today may be obsolete tomorrow. In the span of a decade, we have gone from kilobytes to megabytes, and now, to gigabytes. Within the same duration, processing power has gone from kilohertz to gigahertz. In our lifetime, we have learned how a computer grew from a gigantic calculator to an all purpose gadget in the palm of our hands. This just clearly shows how quickly computer systems evolve; new hardware turn out faster and even better, but is it always a necessity Would you need a three gigahertz processor to do simple word processing. The answer is a resounding no; although times demand that we move forward and move ever so faster; most of use still do the simple things. There are simple tasks that can be done in an Intel Pentium 2 with the same efficiency as a hyper threaded Pentium 4. Although speed and power is so good it is not always necessary; more often than not, we don't use all that speed and power. An average person would be most likely to use a word processor and a browser to focus on mundane paperwork rather than render a 3D replica of Metro Manila. Imagine a hospital low in budget yet abundant with old but working machines. Imagine that the same hospital uses a significant amount of computing power only on rare yet important occasions. Should they spend their money on a machine that will seldom used to its fullest. Would it not be better if the other older computers could borrow some power from this new powerful machine. It is analogous to the inspiration the young gives the old. Consider the University of the Philippines that has lived for decades, it has computers ranging from those that use punch cards to the current machines with piracy-enabled compact disc writers. It has a lot of computers that cannot even compare to today's state of the art machines, yet the full potential of the new, powerful machines are not being fully used. It is a waste of both the old and the new. This is the reason the Linux Terminal Project, or LTSP, is a promising field of research. It has been used in hospitals and other institutions and is undoubtedly applicable to the present condition of schools and universities, especially the good old University of the Philippines. Schhold, for one, need to keep in pace with new trends. However, financial constraints prevent them from acquiring the latest technologies and doing away with old machines. Aside from rare power-intensive instances like graphical rendering, computers will likely be used for simple word processing, browsing the Internet and other academic tasks. New machines will just get worn out without showing what they are made of (and we do not mean silicon). LTSP is a network architecture where thin clients are powered by a high-end server. In such a setup, old machines may still be used, thus, only a few new powerful computers need to be bought. This, in turn, will save on the budget that is continuously being cut in some schools and universities like UP. LTSP is economic, provides the necessary services, and allows veteran computers to relive their glory days. Aside from the possibility that a single point of failure in the server will bring the entire setup crashing down, there does not seem to be any other grave drawback.